Real-time deformation monitoring of bridges using GPS/Accelerometers - Meng, Xiaolin (2002)
The need for conducting real-time bridge deformation monitoring is addressed in the context of the development of bridge management system (BMS) and land transportation safety in this thesis. Current instruments used for bridge dynamic deformation monitoring are compared in terms of system productivity and reliability. An integrated sensor system of Global Positioning System (GPS) receiver and triaxial accelerometer is then proposed with the capabilities to accurately monitor long-term deformation and short-term dynamics of a bridge. Since the investigation of the bridge dynamic responses is of great importance in research and practice, the emphasis of this thesis is on the monitoring of dynamic bridge deformation.